Magnetic resonance imaging studies on acupuncture therapy in cerebral ischemic stroke: A systematic review - Mengyuan Li; Baohui Mu; Mengmeng Li; Xinyu Zhang; Jing Zhang; Haipeng Huang; Hongfeng Wang (Heliyon)
Research has started using Magnetic Resonance Imaging (MRI) to elucidate the action of acupuncture on neuroplasticity following ischemic stroke (IS). Acupuncture is thought to be a potentially beneficial treatment for IS. However, the results remain inconsistent because of MRI processing techniques and study design variations. Therefore, this coordinate-based meta-analysis and systematic review aimed to assess the current state of knowledge about the regional brain fMRI imaging characteristics in acupuncture-treated IS patients. Twenty studies—including 392 IS patients and 256 health controls—met the inclusion criteria after searches via Chinese and English databases. The design techniques utilized in this research were mainly owned before-and-after controlled and randomized controlled trials. Only one study used independent component analysis (ICA), while the majority of MRI analytical techniques focus on functional connectivity (FC) and fractional amplitude of low-frequency fluctuation (fALFF/ALFF). The findings demonstrated a significant rise in the ALFF value of the left supplementary motor region after treatment with acupuncture. The left cerebellum, right inferior frontal gyrus, and hemisphere lobule VIII all showed substantial activation of Reho values. The triangular portion, BA 48, the left inferior network and inferior longitudinal fasciculus, as well as other brain areas decreased in the left inferior frontal gyrus; most research has used FC analysis employing motor areas as seed regions. We found that acupuncture regulated the motor-related network and reorganized the language-related network. Furthermore, acupuncture appears therapeutic for several IS effects, which may be connected to how acupuncture regulates the brain's plasticity.